A randomized, open-label trial of combined nitazoxanide and atazanavir/ritonavir for mild to moderate COVID-19 - Fowotade, Adeola; Bamidele, Folasade; Egbetola, Boluwatife; Fagbamigbe, Adeniyi F.; Adeagbo, Babatunde A.; Adefuye, Bolanle O.; Olagunoye, Ajibola; Ojo, Temitope O.; Adebiyi, Akindele O.; Olagunju, Omobolanle I.; Ladipo, Olabode T.; Akinloye, Abdulafeez; et al. (Frontiers in Medicine, 2022)
Background: The NACOVID trial investigated the efficacy and safety of repurposed nitazoxanide combined with atazanavir/ritonavir for COVID-19. Methods: This is a pilot, randomized, open-label multicentre trial conducted in Nigeria. Mild to moderate COVID-19 patients were randomly assigned to receive standard of care (SoC) or SoC plus a 14-day course of nitazoxanide (1000 mg b.i.d.) and atazanavir/ritonavir (300/100 mg od) and followed through day 28. Study endpoints included time to clinical improvement, SARS-CoV-2 viral load change, and time to complete symptom resolution. Safety and pharmacokinetics were also evaluated (ClinicalTrials.gov ID: NCT04459286). Results: There was no difference in time to clinical improvement between the SoC (n = 26) and SoC plus intervention arms (n = 31; Cox proportional hazards regression analysis adjusted hazard ratio, aHR = 0.898, 95% CI: 0.492-1.638, p = 0.725). No difference was observed in the pattern of saliva SARS-CoV-2 viral load changes from days 2 to 28 in the 35% of patients with detectable virus at baseline (20/57) (aHR = 0.948, 95% CI: 0.341-2.636, p = 0.919). There was no significant difference in time to complete symptom resolution (aHR = 0.535, 95% CI: 0.251 -1.140, p = 0.105). Atazanavir/ritonavir increased tizoxanide plasma exposure by 68% and median trough plasma concentration was 1546 ng/ml (95% CI: 797-2557), above its putative EC90 in 54% of patients. Tizoxanide was undetectable in saliva. Conclusion: Nitazoxanide co-administered with atazanavir/ritonavir was safe but not better than standard of care in treating COVID-19. These findings should be interpreted in the context of incomplete enrolment (64%) and the limited number of patients with detectable SARS-CoV-2 in saliva at baseline in this trial.